2020
DOI: 10.3847/1538-4357/abac17
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Kinematic Evidence of Gravitational Instability

Abstract: Observations with the Atacama Large Millimeter/Submillimeter Array (ALMA) have dramatically improved our understanding of the site of exoplanet formation: protoplanetary disks. However, many basic properties of these disks are not well understood. The most fundamental of these is the total disk mass, which sets the mass budget for planet formation. Disks with sufficiently high masses can excite gravitational instability and drive spiral arms that are detectable with ALMA. Although spirals have been detected in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 66 publications
1
44
0
Order By: Relevance
“…Given the small number of spirals, gravitational instability however seems a rather unlikely cause for the spiral structure we observe (e.g. Cossins et al 2009;Hall et al 2020). It is worth considering, nevertheless, that several spiral arms could possibly appear as only two or three arms due to resolution effects (Dipierro et al 2014) and the disc around CQ Tau happens to be relatively massive, therefore gravitational instability cannot be ruled out at this point.…”
Section: Discussionmentioning
confidence: 79%
“…Given the small number of spirals, gravitational instability however seems a rather unlikely cause for the spiral structure we observe (e.g. Cossins et al 2009;Hall et al 2020). It is worth considering, nevertheless, that several spiral arms could possibly appear as only two or three arms due to resolution effects (Dipierro et al 2014) and the disc around CQ Tau happens to be relatively massive, therefore gravitational instability cannot be ruled out at this point.…”
Section: Discussionmentioning
confidence: 79%
“…Figure 6 shows moment-1 maps with Keplerian rotation subtracted (with each pixel scaled by its distance from the central sink for clarity) for mass ratios of 0.25 and 0.75. Both discs exhibit the "interlocking finger" pattern predicted by Hall et al (2020) as a characteristic imprint of GI. However, the more massive disc, 𝑞 = 0.75, clearly has more pronounced perturbations, strongly suggesting that, when compared to the less massive disc, GI has a larger influence on its dynamics.…”
Section: Discussionmentioning
confidence: 91%
“…However, the origin of the spiral morphology remains unclear. Possibilities that have been investigated include companions, both stellar and planetary, (Dong et al 2015;Fung & Dong 2015;Dong & Fung 2017;Forgan et al 2018b;Price et al 2018b;Huang et al 2018;Dong et al 2018;Veronesi et al 2019;Shen et al 2020) and gravitational instability (GI) , 2005Cossins et al 2009;Dong et al 2015;Hall et al 2016;Meru et al 2017;Forgan et al 2018b;Hall et al 2018;Huang et al 2018;Hall et al 2019Hall et al , 2020Cadman et al 2020b;Chen et al 2021). While it has been demonstrated that GI can be responsible for spiral morphology of some observed discs, it requires the disc-to-star mass ratio, 𝑞, be 0.1 for the spirals to be observable (Cossins et al 2010;Dipierro et al 2014;Dong et al 2015;Hall et al 2016;Kratter & Lodato 2016;Hall et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although spirals and rings are indications of the existence of planets, they can also possibly result from mechanisms that do not involve planets (e.g., spirals: Dong et al 2015a;Montesinos & Cuello 2018;Hall et al 2020, gaps: Birnstiel et al 2015van der Marel et al 2018). Although the formation of spirals in protoplanetary disks can be caused both with and without planets, the differing mechanisms may be distrinugishable via the structure in the disk.…”
Section: Introductionmentioning
confidence: 99%